Particulate and gaseous emissions from different wood fuels during combustion in a small-scale biomass heating system. (May 2017) - Olave, R.J.; Forbes, E.G.A.; Johnston, C.R.; Relf, J.
Abstract: Woodchip is widely used as fuel in dedicated biomass and, even in some conventional energy generation plants. However, there are concerns about atmospheric air pollution from flue gases emitted during wood biomass combustion, particularly oxides of nitrogen (NO x ) and particulates <10 μm diameter (PM10). In the United Kingdom (UK) a small scale biomass heat generation support scheme, the Renewable Heat Incentive (RHI), has been introduced. Qualifying criteria for this scheme have included limits for flue gas emissions of NO X and PM10 of 150 and 30 g per gigajoule (g/GJ) of energy input, respectively. In an experiment, three locally available types of Willow ( Salix spp) and one of Sitka spruce ( Picea sitchensis ) woodchips, showed significant differences in physical and chemical constituents, gaseous and particulate emissions. During combustion in a 120 kW biomass system, air flows, flue gas temperatures and energy output correlated with gaseous emissions, NO x with raw fuel ash, nitrogen, phosphorus and potassium content, as did all flue gas particulate fractions. PM10 ranged from 30.3 to 105.7 g/GJ and NO x from 91.2 to 174.3 g/GJ. Sitka spruce produced significantly lower emissions of PM10 and NOx (27.5 and 52.6% less, respectively) than the three willow fuels, from which emissions were above the RHI emissions limits. Highlights: Qualifying criteria for flue gas emissions of NO X and PM10 during wood biomass combustion are investigated. Willow ( Salix spp) and Sitka spruce ( Picea sitchensis ) biomass, had differences in gaseous and particulate emissions. Fuel emissions is a direct result of using different types of wood biomass fuels. Only Sitka spruce would have qualified for the Renewable heat incentive emission criteria.